Exosomal noncoding RNA (ncRNA) in breast cancer pathogenesis and therapy; two sides of the same coin - Ibrahim, Fatma Magdi; Saleh, Raed Obaid; Uinarni, Herlina; Bokov, Dmitry Olegovich; Menon, Soumya V.; Zarifovich, Khamdamov Baxtiyor; Misra, Neeti; Al-Hamdani, Mais Mazin; Husseen, Beneen; Jawad, Mohammed Abed (Experimental cell research, 2025)
Over the past few years, breast cancer has become the most prevalent type of cancer globally, with the primary cause of death from the disease being metastatic cancer. This has led to the development of early detection techniques, mainly using non-invasive biomarkers in a range of body fluids. Exosomes are unique extracellular vesicles (EVs) transmitting cellular signals over great distances via various cargo. They are readily apparent in physiological fluids due to release by breast cancer cells or breast cancer-tumor microenvironment (TME) cells. In light of this, numerous biological and functional facets of human tumours, such as breast cancer, are intimately associated with exosomal noncoding RNAs (ncRNAs), containing miRNAs (microRNAs), lncRNAs (long noncoding RNAs), and circRNAs (circular RNAs). Exosomal ncRNAs serve a critical role in various steps of breast cancer development, enabling the exchange of genetic information between cancer cells and other cells (e.g., immune cells), thus regulating tumour angiogenesis, growth, metastasis, immune responses and drug resistance. They interact with multiple regulatory complexes with dissimilar enzymatic actions, which, in turn, modify the chromatin sceneries, including nucleosome modifications, DNA methylation, and histone modifications. Herein, we look into the exosomes' underlying regulatory mechanisms in breast cancer. Furthermore, we inspect the existing understanding of the functions of exosomal miRNAs, lncRNAs, and circRNAs in breast cancer to authenticate their possible significance in identifying biomarkers, deciphering their role in immune escape and drug resistance, and finally, analyzing treatment practices. •Exosomes are apparent in physiological fluids as a result of release by breast cancer cells or breast cancer-tumor microenvironment (TME) cells.•They interact with multiple regulatory complexes with dissimilar enzymatic actions, which in turn, modify the chromatin sceneries.•Exosomal ncRNAs alter nucleosome modifications, DNA methylation, and histone modifications in breast cancer.